Biologics and airway remodeling in severe asthma. Issue 12 (23rd August 2022) - Varricchi, Gilda; Ferri, Sebastian; Pepys, Jack; Poto, Remo; Spadaro, Giuseppe; Nappi, Emanuele; Paoletti, Giovanni; Virchow, Johann Christian; Heffler, Enrico; Canonica, Walter G.
Abstract: Asthma is a chronic inflammatory airway disease resulting in airflow obstruction, which in part can become irreversible to conventional therapies, defining the concept of airway remodeling. The introduction of biologics in severe asthma has led in some patients to the complete normalization of previously considered irreversible airflow obstruction. This highlights the need to distinguish a "fixed" airflow obstruction due to structural changes unresponsive to current therapies, from a "reversible" one as demonstrated by lung function normalization during biological therapies not previously obtained even with high‐dose systemic glucocorticoids. The mechanisms by which exposure to environmental factors initiates the inflammatory responses that trigger airway remodeling are still incompletely understood. Alarmins represent epithelial‐derived cytokines that initiate immunologic events leading to inflammatory airway remodeling. Biological therapies can improve airflow obstruction by addressing these airway inflammatory changes. In addition, biologics might prevent and possibly even revert "fixed" remodeling due to structural changes. Hence, it appears clinically important to separate the therapeutic effects (early and late) of biologics as a new paradigm to evaluate the effects of these drugs and future treatments on airway remodeling in severe asthma.